Partisipasi Masyarakat Dalam Pengelolaan APBDes UntukMewujudkan Pemerintahan Yang Good Governance (Studi Kasus Di Desa Banyuurip Kecamatan Klego KabupatenBoyolali Tahun 2016) - Setiawan, M. Wahyu, Dr. Ahmad Muhibbin, M.Si (2016)
This study aimed to describe management form APBDes to make government good governance, describing the community participation in the management of APBDes Village Banyuurip District of Klego Boyolali, and describe the barriers that can reduce public participation in the management of APBDes and solutions to overcome them in the village of Banyuurip Subdistrict Klego Boyolali. This research was qualitative. Subjects in this study are all members of the community in the village Banyuurip Klego District of Boyolali. The object of this research is community participation in the management of APBDes. Data collection techniques in this study were interviews, observation, documentation, and literature review. Mechanical validity of research data using a triangulation of data between the data source. The results of data analysis can be concluded that: 1) Form of management to make government APBDes good governance include transparency, accountability, and participation. 2) Community participation in the management of APBDes Village Banyuurip District of Klego Boyolali include attendance in an activity discussion APBDes, in planning an activity that comes from APBDes, in the handling of a problem that arises in society, are willing to provide assistance in the form of money or goods if the village budget limited, provide assistance in the form of services or skills, give suggestions and opinions regarding priority programs financed ABPDes, willing to be responsible for the activities or proposals presented, are willing to hold the mandate for a position on the proposed citizens, and are willing to carry out the tasks mandated citizens. 3) barriers, which reduce community participation factors include gender, age, level of education, level of income and livelihood, while solutions do is change the meeting schedule of the working day being a holiday, the village must be very clever to choose a language that is easy understood by the public especially the middle class down, the village providing a form that can be filled by the public to be brought home to be collected again, the solution is to do is to give the types of the dues, including the type A (entrepreneur), B (employees ), and C (workers), the village government will give reward to people in the middle to lower who have the skills appropriate their wages every day, citizens are given the opportunity to hold the mandate of office, the village government provides assistance and oversight and direction to the citizens for the first time to hold the mandate positions from start to finish. Keywords: participation, APBDes, Good Governance